Perbandingan Angka Kematian Terapi Antiviral Favipiravir dan Remdesivir pada Pasien COVID-19 Di RSUP Dr. Sardjito Yogyakarta - Nova Satriyani; Fita Rahmawati; Tri Murti Andayani (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2023)
Antiviral treatment for SARS-CoV2 (Severe Acute Respiratory Syndrome Coronavirus-2) is still being studied for its effectivity. The antivirals in the July 3, 2021 edition of the COVID-19 management guidelines, namely favipiravir and remdesivir, are used for moderate, severe and critical degrees. The study compares the mortality rate of COVID-19 patients taking the antivirals favipiravir and remdesivir. This research is a retrospective cohort study conducted at RSUP Dr. Sardjito Yogyakarta. The data was from the medical records of patients diagnosed with moderate, severe, and critical degrees of COVID-19 treated during the January-December 2021 period. Ninety-nine patients (50.8%) used favipiravir, while 97 patients (49.5%) used remdesivir. Chi-square analysis and multiple logistic regression were used to determine the relationship between research variables. Study subjects with the highest percentage of age 46-65 years (65%), male sex (54,6%), comorbid diabetes mellitus and hypertension (13,3%), severe degree of severity (60,7%), and viral load CT value ≤ 29 (80,1%), the patient went home alive (61,2%), and died (38,8%). The antivirals did not affect on mortality (p > 0,05). Further research is needed with the same characteristics of the two groups involving factors of degree severity of the disease, co-morbidity, and other medication therapy.